Pengetahuan Ibu Hamil Tentang Manfaat Asam Folat Selama Kehamilan - Risa Mundari (Jurnal Ilmu Gizi Indonesia (JIGZI), 2020)
The nutritional intake of pregnant women is an important factor both for the fulfillment of nutrition for pregnant women or for the growth and development of the fetus in the womb. In fact, it can reduce the risk of chronic disease in children in the future. The body will go through many physical and hormonal changes during pregnancy. The nutritional needs in question are not in terms of meal portions, but more than that, such as micronutrients and macronutrients, to support the health of pregnant women and fetuses. The need for each type of nutrition during pregnancy is certainly different from the nutritional needs when not pregnant. During pregnancy, you need an additional 300 calories, especially in the second and third trimesters. The daily needs of pregnant women are 1000-1200 milligrams of calcium, 600-800 micrograms of folate, and 27 milligrams of iron (Levine et al., 2018).                    Descriptive research method aims to get an accurate picture of a number of characteristics of the problem under study, namely to see the frequency distribution of each variable. The population in this study were all pregnant women who had their pregnancy checked at BPM Sri Rezeki Rawa Laut Bandar Lampung in June - July 2020.                    Samples were taken as many as 94 people using a large sampling technique using accidental sampling technique. The data collection instrument in this study was a questionnaire containing questions about the knowledge of pregnant women about the benefits of folic acid. The data analysis technique that will be used in this research is univariate data analysis.                    The conclusion is that the overall knowledge of pregnant women about folic acid consumption shows that as many as 8 respondents (8.51%) have good knowledge, 37 respondents (39.36%) have sufficient knowledge, and 49 respondents (52.13%) have less knowledge.                    The participation of health workers in every pregnant woman who performs a pregnancy check can be given counseling about the consumption of folic acid so that it can increase the knowledge of the pregnant woman.